Performing obligatory prayer while hospitalised: perspectives of Muslim patients in a teaching hospital in Malaysia - Abdul Halim, Ratna Zuhairah; Saidi, Sanisah; Mohd Yusof, Nazri; Che Ahmad, Aminudin; Hassan, Nor Haty; Susanti, Suryane (Penerbit UIS, 2024)
Supporting obligatory prayer for patients has become the focus of the healthcare system in Malaysia since the 1990s. Despite frameworks, guidelines, and facilities for the patients, recent studies have reported the number of patients who perform obligatory prayers at the hospital is still low. The reasons for this are unclear. In understanding the issue, this study explores the challenges of Muslim patients in performing prayer during hospitalisation. Using a qualitative single-embedded case study design, adult Muslims admitted to a teaching hospital on the East Coast of Malaysia for over 24 hours and fluent in Malay or English were recruited. Data were collected between October 2021 and August 2022 through in-depth interviews, observations, and document analysis. The data were analysed using the framework technique facilitated by NVivo software version 12. 18 participants were involved, and several themes emerged: perceptions towards Allah and misconceptions about leniency, feelings of uncleanliness and unsuitability to pray, and insufficient support. Despite being aware of the prayer obligation, patients' misconceptions about leniency led to disengagement from prayer activities.